Evaluate The Performance Of The Control And Reduction Of Scour Protection Of Bridge Piers Cylindrical Candles - Seyed Amir Hossein Mahmoudi; Manuchehr Heydarpur (مهندسی و مدیریت ساخت)
Scouring is one of the most important issues in river engineering. A large number of bridges are destroyed worldwide every year, largely due to construction. But because they do not consider the role of hydraulic design in their design. Determining the depth of scouring is important because it indicates the potential for destruction of the flow around the structure. Therefore, it is necessary to predict the scouring pattern for safety in structures that are exposed to water. One of the methods for controlling and reducing scouring can be the use of roughness, collar, submersible plates and protective piles. In the present study, the effect of protective piles on controlling and reducing scour around the cylindrical supports has been investigated. In this study, protective candles with triangular arrangement and constant number of 5 candles were used. In this study, with the constant consideration of most of the parameters in the arrangement of the desired piles, only by changing the two main parameters of the angle of the vertex and the horizontal distance of the piles are distinguished from one another. The facials tested were tested and compared on a base of 3 centimeters at two angles of the vertices of 30 and 45 degrees and the horizontal distance of the piles of 0.7, 1, 1.3 times the diameter of the base. The results of the experiments showed that the efficiency of the pile is increased by decreasing the vertex angle or reducing the horizontal distance of the piles.465